2017
DOI: 10.22616/erdev2017.16.n038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of the RORC, BGH, BGHR, LEP, LEPR genes in Russian hornless cattle breed

Abstract: Abstract. The purpose of this work is to describe the new beef breed Russian Hornless in terms of the genes associated with the formation of economically valuable traits (RORC, bGH, bGHR, LEP, LEPR) and to evaluate its genetic potential in comparison with the parent Aberdeen-Angus breed. The significant differences were found for the LEPR gene: the C allele, the C/C (t d = 3.981, p < 0.001) and C/T (25 % and 1.7 % for Russian Hornless and Aberdeen Angus, respectively) genotypes. Both breeds were registered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies have been revealed that leptin acts via leptin receptor, regulating the satiety and fat deposition [49,50]. To date, LEPR has been widely reported to be related to meat, milk, reproduction, and growth traits in cattle [51][52][53][54][55]. We detected two non-synonymous mutations (rs43347904, g.79,817,216: G > A, exon3, p.S6F; rs43347906, g.79,817,216: C > A, exon4, p.V35L) within the LEPR gene.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been revealed that leptin acts via leptin receptor, regulating the satiety and fat deposition [49,50]. To date, LEPR has been widely reported to be related to meat, milk, reproduction, and growth traits in cattle [51][52][53][54][55]. We detected two non-synonymous mutations (rs43347904, g.79,817,216: G > A, exon3, p.S6F; rs43347906, g.79,817,216: C > A, exon4, p.V35L) within the LEPR gene.…”
Section: Discussionmentioning
confidence: 99%